2014
DOI: 10.4103/2230-8598.144125
|View full text |Cite
|
Sign up to set email alerts
|

The link between HIV/AIDS and violence among young adults: A study in Udupi, Karnataka

Abstract: Background: Violence is a major public health problem which affects the community and threatens the life of people. Objectives: To estimate the prevalence and different forms of violence among HIV positive young adults taking antiretroviral therapy (ART) in Udupi district. Materials and Methods: A cross-sectional study was carried out among HIV positive young adults (18-35 years) who were aware of their status. The participants were selected from ART Centre of Udupi district adopting convenience sampling. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…The prevalence of sexual violence was 74.8% in our study, a figure much higher than reported from developed and developing countries (20,23,31,32). A meta-analysis in the United States of America showed the prevalence of intimate partner violence was 55.3% in HIV-positive women, and 30% of these women had experienced posttraumatic stress disorder (32).…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…The prevalence of sexual violence was 74.8% in our study, a figure much higher than reported from developed and developing countries (20,23,31,32). A meta-analysis in the United States of America showed the prevalence of intimate partner violence was 55.3% in HIV-positive women, and 30% of these women had experienced posttraumatic stress disorder (32).…”
Section: Discussioncontrasting
confidence: 63%
“…These figures are higher than other developing countries. A study from India reported the prevalence of physical violence in HIV-positive adults was 14.5%: 17.6% in women and 6.9% in men (20). In another Indian study, 42% of female participants reported violence, of whom 29% reported physical and 69% reported psychological abuse (21).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation